2015
DOI: 10.1111/dgd.12194
|View full text |Cite
|
Sign up to set email alerts
|

Periostin, a neurite outgrowth‐promoting factor, is expressed at high levels in the primate cerebral cortex

Abstract: Periostin (POSTN or osteoblast specific factor) is an extracellular matrix protein originally identified as a protein highly expressed in osteoblasts. Recently, periostin has been reported to function in axon regeneration and neuroprotection. In the present study, we focused on periostin function in cortical evolution. We performed a comparative gene expression analysis of periostin between rodents (mice) and primates (marmosets and macaques). Periostin was expressed at higher levels in the primate cerebral co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Few studies have explored the role of periostin in neurological diseases till now. Matsunaga et al reported that periostin was expressed at higher level in primate cerebral cortex than mouse cerebral cortex and periostin exhibited neurite outgrowth activity in brain tissues . Recent studies have revealed that periostin was overexpressed in neural stem cell (NSCs) following hypoxia ischemia and hypoxia could increased periostin expression .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have explored the role of periostin in neurological diseases till now. Matsunaga et al reported that periostin was expressed at higher level in primate cerebral cortex than mouse cerebral cortex and periostin exhibited neurite outgrowth activity in brain tissues . Recent studies have revealed that periostin was overexpressed in neural stem cell (NSCs) following hypoxia ischemia and hypoxia could increased periostin expression .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified periostin as a biomarker of inflammation and oxidative stress and evidences also showed that periostin played a key role in promoting tumor progression under hypoxia . What's more, Matsunaga E reported that periostin was expressed at higher level in primate cerebral cortex than mouse cerebral cortex and what's more, periostin exhibited neurite outgrowth activity . Periostin was observed in neurons and increased in astrocytes at 24 hours after transient middle cerebral artery occlusion (tMCAo), which indicated that periostin might play an important role in the pathologic process after stroke .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periostin is a matricellular protein that mediates adaptive response of cortical bone to loading; periostin deficiency has significant negative consequences on bone materials properties, damage accumulation and repair, including local modeling/remodeling in response to fatigue; at the same time, periostin exerts a neuroprotective effect and enhances cortical plasticity [42]. …”
Section: Discussionmentioning
confidence: 99%
“…Perfusion and preparation of frozen sections of macaque monkeys were performed as previously described (Matsunaga et al 2015b). To prepare RNAs for microarray analysis or quantitative reverse transcriptionpolymerase chain reaction (qRT-PCR), we cut some serial sections at a 50 lm thickness (1 mm interval) and dissected brain slices with scalpels in a cold chamber.…”
Section: Sample Preparation Of Macaques For Gene Expression Analysismentioning
confidence: 99%